The Influence of Capital Structure Towards Profitability (Study on Hotel and Tourism Companies that listed in Indonesia Stock Exchange) - Winantea, Yoga (Jurnal Ilmiah Mahasiswa FEB, 2013)
Hotel and tourism companies are one of the company that make a growth of the country nowadays. In the year 2013 the increasing of local tourism has been growth till 245 million of journeys, and will be twice increase in the year 2022 that will be 400 million of journeys. With the increasing of the journeys mean the company need to consider their capital structure perfectly to get maximum profit. This research is aimed to see the influences of Capital Structure toward Profitability and understanding the factor of capital structure which one is the most affected factor toward the profitability in the hotel and tourism companies. There are Long Term Debt to equity and Time Interest Earned as the independent variable and Return On Equity as the dependent variable. This research is explanatory research, which is mean to explain the influences of LTD and TIE toward ROE. This study identifies which variable from capital structure that can be a strong impact toward the profitability. Is the Long Term Debt to equity or Time Interest Earned have the strongest impact toward Return On Equity, and also identifies both LTD and TIE influences toward ROE. The population of the sampling is 21Â  hotel and tourism companies that listed in Indonesia Stock Exchange, and only 6 companies that have the criteria for the research. The research instruments are tested by classic assumption test, which is consist of data normality, multicollinearity, heteroscedastisity, and autocorrelation test. The result is Long Term Debt to equity and Time Interest Earned have simultaneous significantly influences toward Return On Equity. Long Term Debt to equity has the strongest impact toward the Return On Equity. The contribution of each variable is LTD have a negative impact toward ROE and TIE have a positive impact toward ROE. Which is mean that if LTD increasing then ROE will be decreasing, and if TIE increasing ROE will be increasing. The company needs to consider about debt that used, because it can increase the risk of the capital. Keywords : Long Term Debt to equity, Time Interest Earned, Return On Equity